2022
DOI: 10.5271/sjweh.4048
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in proportionate mortality due to COVID-19 by occupation in England and Wales

Abstract: Evidence on the proportionate odds of COVID-19 death over the full course of the pandemic (January 2020 -October 2021) in England and Wales. Several occupations (such as healthcare professionals and associates and medical support staff) had a higher proportion of COVID-19 deaths compared to non-essential workers, but these differences reduced over the pandemic, with the exception of taxi drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
3
24
1
Order By: Relevance
“…From studies to date, the main risk factor identified for workplace transmission is contact with patients with Covid‐19, identified in multiple studies, with the use of respiratory protection 11–15 and vaccination 16,17 mitigating that risk 18 . The excess Covid‐19 mortality seen in HCWs in the United Kingdom in the period to September 2020 was no longer evident in later time periods, presumably reflecting rapid access to vaccinations and improved infection controls at the workplace 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From studies to date, the main risk factor identified for workplace transmission is contact with patients with Covid‐19, identified in multiple studies, with the use of respiratory protection 11–15 and vaccination 16,17 mitigating that risk 18 . The excess Covid‐19 mortality seen in HCWs in the United Kingdom in the period to September 2020 was no longer evident in later time periods, presumably reflecting rapid access to vaccinations and improved infection controls at the workplace 19 …”
Section: Introductionmentioning
confidence: 99%
“…18 The excess Covid-19 mortality seen in HCWs in the United Kingdom in the period to September 2020 was no longer evident in later time periods, presumably reflecting rapid access to vaccinations and improved infection controls at the workplace. 19 Identification of risk factors other than the place of work or professional role requires contemporary collection of exposure data to reflect events at the time the infection occurred. Ideally, this would be through frequent (daily 7 or weekly 20 ) exposure questionnaires administered repeatedly during a prospective study, but the cost and risk of participant reporting fatigue make this approach difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HCWs) were at increased risk of Covid-19 infection early in the Covid-19 pandemic [1] [2], but there is some evidence that this excess risk decreased as the pandemic moved forward [3] [4] [5] [6]. It is unclear whether this reflected improved workplace infection prevention and control practices, vaccination or a combination of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 In the UK, rates of SARS-CoV-2 infection and COVID-19related mortality have been shown to vary by occupational group and have also changed over the course of the pandemic. [3][4][5][6][7][8] Such variations could be related to differences in the working environment particularly exposure to other infected people, e.g. the ability to physically distance, indoor versus outdoor working, surface contacts [9][10][11] , differences in vaccination rate within the workforce 12 13 , differences in infection mitigation strategies 14 and the relaxation of these over time.…”
Section: Introductionmentioning
confidence: 99%